Resilient biomass-derived hydrogel with tailored topography for highly efficient and long-term solar evaporation of high-salinity brine. Issue 43 (16th September 2020) - Chen, Xiaoxiao; Wu, Zhiying; Lai, Dengguo; Zheng, Min; Xu, Lei; Huo, Jiangbo; Chen, Zhangxu; Yuan, Baoling; Fu, Ming-Lai
Abstract : A sponge-like biomass-derived hydrogel is constructed via a facile and scalable strategy, and exhibits promising applications in solar-driven seawater desalination, zero-liquid discharge and solute recovery. Abstract : Solar-driven steam generation is an emerging, attractive, and sustainable technology for potential seawater desalination and wastewater purification. Despite the tremendous progress to date, some technological gaps still remain such as the seemingly unavoidable salt accumulation on the solar absorbers and the generally costly and delicate nanostructures. Here, a cost-effective biomass-derived hydrogel with rationally architected sponge-like skeletons is fabricated through a facile and scalable foaming-polymerization strategy. With advantageous features of organic-polymer chains, inorganic-particles and hierarchical bubble templates, the constructed hydrogel exhibits well-interpenetrative channels and unique porous topography with excellent resilience, fast water-transfer and enhanced light-trapping performances, leading to an ultrahigh and long-term stable evaporation rate of 1.77 ± 0.05 kg m −2 h −1 at 1 sun illumination out of high-salinity seawater (25 wt%) over the entire 7 12 h cycles without deterioration. This promising performance outperforms all the pioneering reported low-cost carbon-based solar absorbers for high-salinity desalination. Importantly, the salt accumulation prefers to crystalize around the edges, spatially isolated from the steam generation surface, achieving complete separation between water and solute. This simple technology to turn "waste" biomass to efficient solar-driven evaporators is anticipated to offer new possibilities to continuously and economically produce pure water from seawater and solute recovery.